Infinite Trig Sum

Algebra Level 2

cot 1 3 + cot 1 7 + cot 1 13 + cot 1 21 + cot 1 31 + \cot^{-1} 3 + \cot^{-1} 7 + \cot^{-1} 13 + \cot^{-1} 21 + \cot ^ {-1} 31 + \ldots

Evaluate the sum above in degrees.


The answer is 45.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

The series can be written as

n = 1 cot 1 ( n 2 + n + 1 ) = n = 1 tan 1 1 ( n 2 + n + 1 ) \displaystyle\sum_{n=1}^{\infty} \cot^{-1}(n^{2} + n + 1) = \sum_{n=1}^{\infty} \tan^{-1} \frac{1}{(n^{2} + n + 1)} .

Next, using the fact that

tan 1 ( x ) tan 1 ( y ) = tan 1 ( x y 1 + x y ) \tan^{-1}(x) - \tan^{-1}(y) = \tan^{-1}(\frac{x - y}{1 + xy})

let x = n + 1 x = n + 1 and y = n y = n to see that

tan 1 ( n + 1 ) tan 1 ( n ) = tan 1 1 ( n 2 + n + 1 ) \tan^{-1}(n + 1) - \tan^{-1}(n) = \tan^{-1} \dfrac{1}{(n^{2} + n + 1)} .

Our series can then be written as

n = 1 ( tan 1 ( n + 1 ) tan 1 ( n ) ) \displaystyle\sum_{n=1}^{\infty} (\tan^{-1}(n + 1) - \tan^{-1}(n)) ,

which is a telescoping series, giving a sum of

tan 1 ( 1 ) + lim n ( tan 1 ( n + 1 ) ) = π 4 + π 2 = π 4 -\tan^{-1}(1) + \lim_{n \rightarrow \infty} (\tan^{-1}(n + 1)) = -\dfrac{\pi}{4} + \dfrac{\pi}{2} = \dfrac{\pi}{4} ,

which in degrees is 4 5 \boxed{45^{\circ}} .

N.C.E.R.T Problem Nicely presented. upvoted

U Z - 6 years, 6 months ago

I PROTEST! The next term in the sequence was actually π ! \pi! Yes that is pi factorial!

THIS PROBLEM IS WRONG!!!

But really the sequence must be clearly defined. For example, polynomial interpolation could be used to show that the next term in the sequence is indeed π ! \pi! :

See Wolfram|Alpha


(P.S. nice solution Brian ;))

John M. - 6 years, 5 months ago

Nice I even did in same way

Satish Pandala - 2 years, 6 months ago

Practically no other way to find that to use the arctan addition formula.

Maxence Seymat - 2 years, 1 month ago

One more term should have been given... I thought the series was 3, 7, 13, 17, 23...

Bhaskar Sukulbrahman - 6 years, 6 months ago

Log in to reply

There is no 17 in it

Neelotpal Dutta - 5 years, 3 months ago

Log in to reply

I think it has been edited now. There were few terms last time I see.

Bhaskar Sukulbrahman - 5 years, 3 months ago
Ariel Gershon
Dec 15, 2014

First you have to figure out that the n t h n^{th} term is c o t 1 ( n 2 + n + 1 ) cot^{-1}(n^2 + n + 1) (that should be more clear, by the way).

Recall that the tangent sum formula states that t a n ( a + b ) = t a n ( a ) + t a n ( b ) 1 t a n ( a ) t a n ( b ) tan(a+b) = \frac{tan(a)+tan(b)}{1-tan(a)tan(b)} . Now let p = t a n ( a ) p = tan(a) and q = t a n ( b ) q = tan(b) . Then if 9 0 o < t a n 1 ( p ) + t a n 1 ( q ) < 9 0 o -90^o < tan^{-1}(p) + tan^{-1}(q) < 90^o , we have t a n 1 ( p ) + t a n 1 ( q ) = t a n 1 ( p + q 1 p q ) tan^{-1}(p) + tan^{-1}(q) = tan^{-1} \left(\frac{p+q}{1-pq} \right) Now if we let x = 1 p x = \frac{1}{p} and y = 1 q y = \frac{1}{q} , then this becomes: t a n 1 ( 1 x ) + t a n 1 ( 1 y ) = t a n 1 ( x + y x y 1 ) tan^{-1} \left(\frac{1}{x} \right) + tan^{-1} \left( \frac{1}{y} \right) = tan^{-1} \left(\frac{x+y}{xy-1} \right) c o t 1 ( x ) + c o t 1 ( y ) = c o t 1 ( x y 1 x + y ) ( ) cot^{-1} (x) + cot^{-1} (y) = cot^{-1} \left(\frac{xy-1}{x+y} \right) (*)

Using this formula, I calculated the first few partial sums. They turned out to be c o t 1 ( 3 1 ) , c o t 1 ( 4 2 ) , c o t 1 ( 5 3 ) , . . . cot^{-1} \left(\frac{3}{1}\right), cot^{-1}\left(\frac{4}{2}\right), cot^{-1} \left(\frac{5}{3} \right), ...

So we can prove by induction that the n t h n^{th} partial sum is equal to c o t 1 ( n + 2 n ) cot^{-1} \left(\frac{n+2}{n}\right) . This is very easy using formula ( ) (*) above:

The base case n = 1 n = 1 is clearly true since c o t 1 ( 3 ) = c o t 1 ( 1 + 2 1 ) cot^{-1}(3) = cot^{-1}\left(\frac{1+2}{1}\right) .

Now suppose the k t h k^{th} partial sum is c o t 1 ( k + 2 k ) cot^{-1}\left(\frac{k+2}{k}\right) . Then the ( k + 1 ) t h (k+1)^{th} partial sum is: c o t 1 ( k + 2 k ) + c o t 1 ( ( k + 1 ) 2 + ( k + 1 ) + 1 ) cot^{-1}\left(\frac{k+2}{k}\right) + cot^{-1}\left((k+1)^2+(k+1)+1\right) = c o t 1 ( k + 2 k ( k 2 + 3 k + 3 ) 1 k + 2 k + k 2 + 3 k + 3 ) = cot^{-1} \left(\frac{\frac{k+2}{k}*(k^2+3k+3) - 1}{\frac{k+2}{k} + k^2+3k+3} \right) = c o t 1 ( k 3 + 5 k 2 + 9 k + 6 k k + 2 + k 3 + 3 k 2 + 3 k ) = cot^{-1} \left( \frac{k^3+5k^2+9k+6 - k}{k+2 + k^3 + 3k^2+3k}\right) = c o t 1 ( ( k + 3 ) ( k 2 + 2 k + 2 ) ( k + 1 ) ( k 2 + 2 k + 2 ) ) = c o t 1 ( k + 3 k + 1 ) = cot^{-1} \left( \frac{(k+3)(k^2+2k+2)}{(k+1)(k^2+2k+2)} \right) = cot^{-1} \left(\frac{k+3}{k+1} \right) Hence the induction is complete.

Therefore, the infinite sum is equal to lim n c o t 1 ( n + 2 n ) = c o t 1 ( 1 ) = 4 5 o \lim_{n \to \infty} cot^{-1} \left(\frac{n+2}{n}\right) = cot^{-1} (1) = \boxed{45^o}

Chew-Seong Cheong
Dec 16, 2019

Let us define θ n = cot 1 1 + cot 1 3 + cot 1 7 + + cot 1 ( n 2 + n + 1 ) \displaystyle \theta_n = \cot^{-1} 1+\cot^{-1} 3 + \cot^{-1} 7 + \cdots + \cot^{-1} (n^2+n+1) . Then θ n = tan 1 ( n + 1 ) \theta_n = \tan^{-1} (n+1) radians for all integers n 0 n\ge 0 . Let us prove the claim by induction.

For n = 0 n=0 , θ 0 = cot 1 1 = tan 1 ( 0 + 1 ) \theta_0 = \cot^{-1} 1 = \tan^{-1} (0+1) , therefore the claim is true for n = 0 n=0 . Assuming that the claim is true for n n , then for n + 1 n+1 :

θ n + 1 = θ n + cot 1 ( ( n + 1 ) 2 + ( n + 1 ) + 1 ) = tan 1 ( n + 1 ) + tan 1 1 ( n + 1 ) 2 + ( n + 1 ) + 1 = tan 1 ( n + 1 + 1 ( n + 1 ) 2 + ( n + 1 ) + 1 1 n + 1 ( n + 1 ) 2 + ( n + 1 ) + 1 ) = tan 1 ( ( n + 1 ) 3 + ( n + 1 ) 2 + ( n + 1 ) + 1 ( n + 1 ) 2 + 1 ) = tan 1 ( ( n + 1 ) + 1 ) \begin{aligned} \theta_{n+1} & = \theta_n + \cot^{-1} ((n+1)^2 + (n+1)+1) \\ & = \tan^{-1} (n+1) + \tan^{-1} \frac 1{(n+1)^2+(n+1)+1} \\ & = \tan^{-1} \left(\frac {n+1+\frac 1{(n+1)^2+(n+1)+1}}{1-\frac {n+1}{(n+1)^2+(n+1)+1}}\right) \\ & = \tan^{-1} \left(\frac {(n+1)^3+(n+1)^2+(n+1)+1}{(n+1)^2+1} \right) \\ & = \tan^{-1} ((n+1)+1) \end{aligned}

The claim is also true for n + 1 n+1 , therefore it is true for all n 0 n \ge 0 .

Note that θ n \theta_n includes an additional initial term of cot 1 1 \cot^{-1} 1 , therefore the answer we need to find is

lim n θ n cot 1 1 = lim n tan 1 ( n + 1 ) π 4 = π 2 π 4 = π 4 = 45 \begin{aligned} \lim_{n \to \infty} \theta_n - \cot^{-1} 1 & = \lim_{n \to \infty} \tan^{-1}(n+1) - \frac \pi 4 \\ & = \frac \pi 2 - \frac \pi 4 = \frac \pi 4 = \boxed{45}^\circ \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...